[BP.10.01] PROGNOSTIC SIGNIFICANCE OF REVERSE DIPPING PATTERN IN HYPERTENSION: A META-ANALYSIS. (September 2017) - Gherbesi, E.; Cuspidi, C.; Sala, C.; Tadic, M.; Grassi, G.; Mancia, G.
Abstract : Objective: Findings on the prognostic value of reverse dipping (RD) are scanty, mostly derived from studies in the hypertensive setting. In order to provide a comprehensive information on this issue we performed a meta-analysis of publications providing data on incident non-fatal and fatal cardiovascular (CV) events among subjects categorized as dipper/extreme dipper, non-dipper and RD. Design and method: Studies were identified by crossing the following search terms: "reverse dipping", "inverted dipping", "cardiovascular events", "cardiovascular mortality", "hypertension". Full articles published in English language reporting data from studies performed in hypertensive individuals were considered. Results: Overall, 6918 untreated and treated hypertensive subjects (518 extreme dippers, 2900 dippers, 2722 non-dippers and 696 RDs) of both genders (mean age 62 ± 4 years, 95% CI 54–69 years) were included in five reports (sample size range: 401–3468 participants). A total of 890 cardiovascular events (12.9%) were recorded across follow-up periods ranging from 41 to 120 months. In the pooled population the risk of non-fatal and fatal cardiovascular events in RDs was 2.5-fold greater (95% CI 2.11–2.96, p < 0.01) than in dippers (Figure) and persisted to be 2.1-fold higher (95% CI 1.77–2.45, p < 0.001) as compared to non-dippers. The risk entailed by the RD pattern remained significantly increased when compared to extreme-dippers. Figure. No caption available. Conclusions: Owing to the high cardiovascular risk entailed by RD, an appropriate anti-hypertensive chrono-therapeutic approach may have relevant implications for cardiovascular prevention. Further studies aimed to clarify whether correction of abnormal circadian pattern may improve the prognosis are needed.